Is Hippocampus hippocampus (Osteichthyes, Syngnathiformes, Syngnathidae) a member of the Romanian ichthyological fauna? - Alexandru Iftime (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2023)
We present a record of Hippocampus hippocampus (the short-snouted seahorse) from a museum collection specimen, arguing that it most likely represents the first known occurrence of this species from the Romanian Black Sea waters.